Pengaruh Nutrisi Bahan Kering dan Serat Kasar Silase Ransum Komplit Berbasis Limbah Ampas Tebu (Bagasse), Indigofera dan Molases - Jati, Putri Zulia; Setiawan, Bagus Dimas (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The potential of bagasse has not been utilized optimally due to its low nutritional content, so it is necessary to add feed ingredients such as indigofera which has high nutrition and molasses which is needed for further processing by means of anaerobic fermentation or silage. This research aims to determine the nutritional quality of complete ration silage based on bagasse, indigofera and molasses with different compositions. This research used a completely randomized factorial design consisting of 2 factors, each treatment unit was repeated 3 times. Factor A is the level of bagasse + indigofera, namely A1 = 100% bagasse + 0% indigofera; A2 = 50% bagasse + 50% indigofera; A3 = 75% bagasse + 25% indigofera and factor B is the molasses level, namely B0 = 5% molasses and B1 = 10% molasses. The variables measured are dry matter and crude fiber. The data obtained were analyzed based on analysis of variance carried out with the Duncan test at 5% and 1% levels. The results of this study showed that there was an interaction between factor A and factor B (P0.01) on the dry matter and crude fiber content. Factor A had a very significant effect (P0.01) on the dry matter and crude fiber content. Factor B had a very significant effect (P0.01) on dry matter but did not affect crude fiber. It was concluded that treatment A2, namely the composition of 50% bagasse + 50% indigofera and treatment B0, namely 5% molasses, could increase the dry matter content and reduce the crude fiber content in complete ration silage based on bagasse.